A Holistic Approach in the Prevention of Type 2 Diabetes Mellitus: Mini Review of Lifestyle Integration Starting from a Young Age - Agustia, Dilma'aarij Riski; Khoiriyah, Fitri; Ananda, Vita; Avrilianda, Devi; Tiara, Fahlani (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Background: Diabetes mellitus is a significant global health problem with increasing prevalence worldwide. This study aims to analyze the existing evidence regarding the prevention of type 2 diabetes mellitus by integrating lifestyle patterns from a young age. Methods: This study is a literature review research that uses guidelines from PROSPERO with prism flow diagram in selecting articles. The keywords used were “Diabetes Mellitus” OR “Diabetes Mellitus Type 2” AND “Young Age” AND “Lifestyle”. Research that discusses the prevention of type 2 diabetes mellitus with a young age lifestyle published between 2023 and 2024 in English and Indonesian. Results: Of the 5 studies analyzed, it was found that effective strategies in preventing type 2 diabetes mellitus, especially at a young age, are a healthy lifestyle, regular exercise, stress management, increasing health literacy and social support from family and environment. Conclusion: prevention of type 2 diabetes mellitus requires a holistic approach that considers various aspects applied from a young age, from early prevention to ongoing management